New Media dan Pergeseran Otoritas Keagamaan Islam di Indonesia - Mutohharun Jinan (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2012)
New media affects fundamental changes in religious life. The change was apparent in the shift from traditional religious authorities, such as ulama (clergy), murshid, religious teachers or ustad, government, and non-governmental organizations, to modern religious authorities. With the waning of traditional religious authority, due to the development of information technology of new media, religious authorities are now in the hand of impersonal media, such as books, websites, blogs, and the like. New media has created new social environments that facilitate spiritual interaction, create new authorities and legitimize actions of the religious community. Progressiveness and openness of new media has driven the acceleration process of “rejuvenation of ulama”.